Diagnostic Value of T1 Slope in Degenerative Cervical Spondylotic Myelopathy - Sun, Jin; Zhao, Hong-Wei; Wang, Jun-Jie; Xun, Liang; Fu, Na-Xin; Huang, Hui (Medical science monitor, 2018)
BACKGROUND To explore the diagnostic value of sagittal measurement of thoracic inlet parameters for degenerative cervical spondylotic myelopathy (DCSM). MATERIAL AND METHODS Sixty patients with DCSM (study group) and the same number of normal subjects (control group) were initially enrolled in the study. All data from X-ray in the standing position and computed tomography (CT) in the supine position were collected and carefully analyzed. Cervical sagittal parameters, including C2-C7 angle, C2-C7 sagittal vertical axis (C2-C7 SVA), T1 slope, thoracic inlet angle (TIA), and neck tilt (NT), were measured at the lateral radiographs by using standard X-rays and CT. Univariate analysis and multivariate logistic regression analysis were carried out to explore the diagnostic value of cervical sagittal parameters for the DCSM. RESULTS All the enrolled patients in the study and control groups completed the follow-up, and the mean follow-up periods were 35.8 months in the study group and 36.3 months in the control group. The DCSM group had smaller T1 slope and TIA when compared with that of the control group (18.14±2.67° vs. 24.16±3.7°, p=0.00; 66.42±12.36° vs. 70.42±10.21°, p=0.01). Logistic regression analysis and receiver operating characteristic (ROC) curve revealed that preoperative T1 slope of less than 18.5° had significant diagnostic value for the incidence of DCSM (p<0.05). CONCLUSIONS Patients with sagittal imbalance of thoracic inlet parameters have higher risk of DCSM, while T1 slope of less than 18.5° showed significant diagnostic value for the incidence of DCSM.